Lifelong learning from the eyes of student leaders : current issues, challenges and expectation - Wardah Mohamad; Wan Rohaida Wan Husin; Tuan Fatma Tuan Sulaiman; Mohd Rizan Ruslan (2014)
Lifelong learning serves as a platform for increasing quality of life. Once learners are enrolled in lifelong learning programmes, they automatically have access to knowledge and are able to increase their capacity to perform better both at home and at work. Opportunities open for either new jobs or increases in salaries in current jobs. This means that lifelong learners are able to improve their quality of life enjoying improved lifestyles and being able to tap into new avenues and opportunities. Lifelong learning has now become integral to the growth of the country. With the introduction of lifelong learning in Malaysia, many programmes have been implemented still many are in the pipeline. It is thus essential that we stop and evaluate at the current status of lifelong learning in the country. This research is part of a bigger research which looks at the success and impact of the National Higher Education Strategic Plan. This paper, will however, present the findings regarding the current issues, challenges and future expectations of student leaders in the country with regard to the implementation of lifelong learning. This is a qualitative study which uses focus groups as its main source of data. Findings show that there are indeed many issues and challenges that are inherent in the country’s pursuit to enculturate lifelong learning. The main finding is that higher education institutions, community colleges and other institutions should provide community service in terms of providing avenues for local community to acquire academic qualification or obtain job-related skills training with minimal entry requirement and flexible learning schedule. (Abstract by authors)